Who Said or What Said? Estimating Ideological Bias in Views Among Economists - Mohsen Javdani; Ha-Joon Chang (Institute of Labor Economics (IZA), 2019)
There exists a long-standing debate about the influence of ideology in economics. Surprisingly, however, there is no concrete empirical evidence to examine this critical issue. Using an online randomized controlled experiment involving 2425 economists in 19 countries, we examine the effect of ideological bias on views among economists. Participants were asked to evaluate statements from prominent economists on different topics, while source attribution for each statement was randomized without participants' knowledge. For each statement, participants either received a mainstream source, an ideologically different less-/non-mainstream source, or no source. We find that changing source attributions from mainstream to less-/non-mainstream, or removing them, significantly reduces economists' reported agreement with statements. This contradicts the image economists have of themselves, with 82% of participants reporting that in evaluating a statement one should only pay attention to its content. Using a framework of Bayesian updating we examine two competing hypotheses as potential explanations for these results: unbiased Bayesian updating versus ideologically-/authority-biased Bayesian updating. While we find no evidence in support of unbiased updating, our results are consistent with biased Bayesian updating. More specifically, we find that changing/removing sources (1) has no impact on economists' reported confidence with their evaluations; (2) similarly affects experts/non-experts in relevant areas; and (3) has substantially different impacts on economists with different political orientations. Finally, we find significant heterogeneity in our results by gender, country, PhD completion country, research area, and undergraduate major, with patterns consistent with the existence of ideological bias.
Keywords: A11; A14; 330; ideology; ideological bias; authority bias; Bayesian updating; views among economists